THE EFFECT OF HPMC GELLING AGENT CONCENTRATION ON THE PHYSICAL PROPERTIES OF ANTI-ACNE SERUM FORMULATION WITH LEMON PEEL EXTRACT - ., Elianasari .; Paramita, Ayu (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2024)
namely flavonoids and alkaloids, which can cause the emergence of acne This study aims to investigate how varying concentrations of HPMC gelling agent F1 (4%), F2(6%) and F3 (8%) affect the physical properties of anti-acne serum formulations containing lemon peel extract. The research method employed is descriptive, based on the evaluation of the physical properties of the serum formulations. Organoleptic observations of F1 and F2 show a yellowish-brown color, solid form, and characteristic smell of lemon extract, while F3 is brown, slightly thick, and has the characteristic smell of lemon peel extract. The pH values of F1, F2, and F3 are 5, indicating neutrality. The homogeneity test shows that all formulations are homogeneous. The adhesive strength of F1, F2, and F3 are 2.16, 2.65, and 3.35 seconds, respectively. The spreading power of F1, F2, and F3 are 7, 6, and 5. The specific gravity of F1, F2, and F3 are 1.508, 1.640, and 1.648 g/mL and the viscosity values are 385.95, 439.79, and 500.63 cps. The variation in HPMC concentration affects the results of the serum formulation tests, including organoleptic observations, spreading power, adhesive strength, specific gravity, and viscosity.